2001
DOI: 10.1191/096120301717164958
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prolactin on signal transduction and gene expression: possible relevance for systemic lupus erythematosus

Abstract: Receptors for prolactin (PRL-R) are expressed in normal leukocytes from rat and man. PRL signals through PRL-R associated Janus tyrosine kinase (Jak)-2 and signal transducers and activators of transcription (Stat). In addition, in human leukocytes PRL also activates the p38 MAP kinase pathway. PRL, at physiological concentrations, stimulates the expression of the interferon regulatory factor (IRF)-1 gene in rat spleen and bone marrow cells. In man, genes induced by PRL include several members of the 'suppresso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 61 publications
2
8
0
Order By: Relevance
“…Serum PRL levels were significantly increased in SLE patients compared to healthy controls, especially in active patients, and were positively correlated with SLEDAI, indicating a possible association with SLE disease activity. The above results confirm most of previous research on correlation between serum PRL and SLE disease activity 18–21 …”
Section: Discussionsupporting
confidence: 91%
“…Serum PRL levels were significantly increased in SLE patients compared to healthy controls, especially in active patients, and were positively correlated with SLEDAI, indicating a possible association with SLE disease activity. The above results confirm most of previous research on correlation between serum PRL and SLE disease activity 18–21 …”
Section: Discussionsupporting
confidence: 91%
“…This pathway involves interferon regulating factor-1 (IRF-1) [57], inducible nitric oxide synthase, and suppressors of cytokine signaling (SOCS)-2, -3, and -7 [58]. Prolactin can also activate other signaling pathways, such as the Src and Tec family of tyrosine kinases, SHP-2 phosphatase, ZAP-7, and MAPK and Fyn [54].…”
Section: Prolactin and Its Receptorsmentioning
confidence: 99%
“…It has been found that prolactin increases the constitutive expression of SOCS-3 in PBMC, and CIS and SOCS-2 in granulocytes [38] . SOCS-2, however, was found to restore prolactin signaling by interfering with the inhibitory activity of SOCS-1 [37] . Since prolactin receptors are expressed on monocytes as well as other leukocytes, prolactin with LPS might enhance the production of IL-10 from monocytes not only through the JAK-STAT pathway but also from MAPK and/or NF-B, in which expression of SOC-3 does not inhibit the latter two pathways [39] .…”
Section: Discussionmentioning
confidence: 94%
“…However, in LPS stimulation, prolactin increased IL-10 concentrations which remained elevated even at high concentrations of prolactin. Recently, prolactin was also found to regulate another family of proteins called the suppressors of cytokine signaling (SCOS) [37] . These SOCS proteins (SOCS 1-7 and cytokine-inducible SH2-domain-containing protein CIS) behave like a negative regulator of cytokine signal transduction pathways mainly by inhibiting the JAK-STAT kinase pathway.…”
Section: Discussionmentioning
confidence: 99%